A New Methodology for the Characterisation of Natural Dyes on Museum Objects Using Gas Chromatography–Mass Spectrometry. (2nd January 2018) - Poulin, Jennifer
ABSTRACT: The derivatising agent m -(trifluoromethyl)phenyltrimethylammonium hydroxide (TMTFTH) has been employed for more than a decade at the Canadian Conservation Institute (CCI) to extract natural dyes from historical textiles and other dyed substrates. The alkaline reagent breaks the bonds between the colourants and the mordant ions or functional groups of the substrate, releasing the dye compounds into the extraction solution, and derivatises polar functionalities to produce compounds that are amenable to subsequent analysis by gas chromatography–mass spectrometry (GC–MS). This approach allows for the identification of the colourants, and is also useful in determining the presence of degradation products from the dyes and substrates, non-dye marker compounds, auxiliary compounds added to the dye bath, and substances present on the object through anthropogenic use, conservation treatments, or possible pesticide contamination. This paper discusses compounds formed through the reactions of TMTFTH with flavonoid dyes (dyer's buckthorn, old fustic, weld, red sandalwood, and brazilwood), quinone dyes (madder, Relbunium, Galium, cochineal, lac, and walnut), indigoid dyes (indigo, Tyrian purple, and indigo carmine), turmeric, marigold, lupin and several lichen species. Results from a selection of historical dyed textiles and other decorative objects analysed at the CCI are provided to illustrate applications of the methodology.